Algoritma Classifier Untuk Menganalisis Faktor Pemilihan Hunian Tempat Tinggal - elisa, erlin (Universitas Putera Batam, 2020)
Batam City is the largest city in the RIAU archipelago, the population is also included in the island with the largest population when compared to other islands. According to data from the Central Statistics Agency (BPS), Batam City recorded the projected population growth in Batam in 2019 as many as 1,376,009 people. The development of the increasing population will gradually start to cause new problems, namely the problem of housing or housing. When viewed from the incident so far, the factors or reasons for choosing a residential place to live are not understood by the community so that when they buy, problems often occur, such as not matching the price or problems with developers such as difficult mortgage management and an unsuitable environment and many problems. other. This study will analyze the choice of residential housing with the C4.5 datamining technique and rapid mining as data testing tools, the results of this study show that the main factors for housing selection are clean water sanitation, accessibility, accessibility and price after testing the accuracy of C4.5 data. 25 sample data obtained 88.00% accuracy of the performance of this algorithm.